Dementia and Parkinson's Disease: Similar and Divergent Challenges in Providing Palliative Care - van der Steen, Jenny T.; Lennaerts, Herma; Hommel, Danny; Augustijn, Bertie; Groot, Marieke; Hasselaar, Jeroen; Bloem, Bastiaan R.; Koopmans, Raymond T. C. M. (Frontiers in Neurology, 2019)
Dementia and Parkinson’s disease are incurable neurological conditions. Patients often experience specific, complex and varying needs along their disease trajectory. Current management typically employs a multidisciplinary team approach. Recognition is growing that this team approach should also address palliative care issues to optimize quality of life for patient and family caregivers, but it remains unclear how palliative care is best delivered. To inspire future service development and research, we compare the trajectories and conceptualization of palliative care between dementia and Parkinson’s disease. Both Parkinson’s disease and dementia are characterized by a protracted course, with progressive but fairly insidious development of disability. However, patients with Parkinson’s disease may experience relatively stable periods initially but with time, a wide range of debilitating symptoms develops, many of which do not respond well to treatment. Eventually, dementia develops in most Parkinson patients, while motor disability develops in many dementia patients. In both diseases, symptoms such as pain, apathy, sleeping problems, falls, and a high caregiver burden are prevalent. Advance care planning has benefits in terms of being prepared before the disease progresses into a stage with communication problems or severe cognitive impairment. However, for both conditions, the protracted disease trajectories complicate conceptualization of palliative care through different stages of the disease, with pertinent questions such as when to offer what interventions pro-actively. Given the similarities and differences, we should develop palliative approaches that are partially generic and partially disease-specific. These should be integrated seamlessly with disease-specific care. Substantial research is already being performed on dementia palliative care. This may also inform the further development of palliative care for Parkinson’s disease, including an evaluation of palliative interventions and services.